Analyzing the Activities for Protection of Intellectual Property in Bulgaria for the 2012-2016 Period - Krushkov, Nikolay (Research Papers, 2017)
With the development of technology and global information connectivity, there is a transformation where the "industrial society" turns into an "information society". A characteristic feature of the new, knowledge-driven working is the application of new knowledge to existing knowledge as a major source of productivity.The purpose of the study is to draw conclusions about the trends in the national economy related to its dependence on new knowledge, both in the material and non-material fields.Tasks to achieve the goal are related to identification and analysis of:• Measurable annual indicators of the results of the state authorities competent to enforce intellectual property protection.• Measurable annual indicators of the activity of individuals and companies in the process of obtaining protection of their intellectual property.Industrial Property research of the study has consistently shown a positive upward trend in almost three times of the interest in seeking protection for technical solutions as a utility model. With a negative economic impact, the tendency of low interest towards Bulgarian market by the foreign applicants could be pointed out. Foreign applications for inventions, utility models and trademarks are between 5% and 10% of the total number of applications.Artistic Property research of the study recognizes that the interest in book publishing remains steady, but the brochures grow by almost 20%. There is no change in the presence of theaters and radios, but the interest in cinema and television is growing. A negative trend is only reported in newspapers that are consistently decreasing as headlines and circulation.Simultaneous research of industrial property and artistic property indicators is worthwhile because it allows identification of global trends in intellectual property as a whole.